Integrative analysis of disulfidptosis and immune microenvironment in hepatocellular carcinoma: a putative model and immunotherapeutic strategies - Yang, Ti; Liu, Junhao; Liu, Fang; Lei, Jiashun; Chen, Siliang; Ma, Zengxin; Ke, Peifeng; Yang, Qiaolan; Wen, Jianfan; He, Yifeng; Duan, Juan; Zeng, Xiancheng (Frontiers in Immunology, 2024)
Background Hepatocellular carcinoma (HCC) is a malignant tumor with a high rate of recurrence and metastasis that does not respond well to current therapies and has a very poor prognosis. Disulfidptosis is a novel mode of cell death that has been analyzed as a novel therapeutic target for HCC cells. Methods This study integrated bulk ribonucleic acid (RNA) sequencing datasets, spatial transcriptomics (ST), and single-cell RNA sequencing to explore the landscape of disulfidptosis and the immune microenvironment of HCC cells. Results We developed a novel model to predict the prognosis of patients with HCC based on disulfidptosis. The model has good stability, applicability, and prognostic and immune response prediction abilities. N-myc downregulated gene1 (NDRG1) may contribute to poor prognosis by affecting macrophage differentiation, thus allowing HCC cells to evade the immune system. Conclusions Our study explores the disulfidptosis of HCC cells through multi-omics and establishes a new putative model that explores possible targets for HCC treatment.